Gambaran Perilaku Picky Eater pada Balita Usia 12-36 Bulan di Wilayah Kerja Puskesmas Tatapaan Kabupaten Minahasa Selatan - Theresia Permata Hati Hasibuan; Maureen Irinne Punuh; Afnal Asrifuddin (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Picky eating is an eating behavior in children characterized by a tendency to be selective about food and refuse certain types of food. This behavior is common during the toddler period and may affect nutritional intake if it persists over time. This study aimed to describe picky eating behavior among toddlers aged 12–36 months in the working area of Puskesmas Tatapaan, South Minahasa Regency. A descriptive quantitative design was employed involving 81 toddlers selected through proportionate stratified random sampling. Data were collected using the Child Eating Behaviour Questionnaire (CEBQ) and analyzed using univariate analysis. The results showed that 58 toddlers (71.6%) exhibited a tendency toward picky eating behavior, while 23 toddlers (28.4%) did not. Most toddlers demonstrated a positive interest in food; however, they also showed sensitivity to satiety and a high desire to drink. In conclusion, picky eating in this study reflected selective eating rather than complete food refusal, indicating that parental education on responsive feeding is essential to optimize children's nutritional intake. This study was limited by the use of parent-reported data and a descriptive design, which may restrict causal interpretation. Therefore, further analytical or longitudinal studies are recommended to identify factors associated with picky eating behavior in toddlers.